DeepL Translate and DeepL Write as Tools for Text Mediation in Plurilingual Workplaces - Klimkowski, Konrad (2023)
This article discusses how machine translation software can be used in developing users’ language and communicative skills in the workplace. The case in point is the neural machine engine DeepL, whose primary functionality is text translation; yet when one thinks about modern workplaces, it turns out that professionals other than translators may be in need of urgent text creation in a foreign language. Knowledge of the target language is an indisputable prerequisite for effective specialist communication. Nonetheless, with the use of a machine translator like DeepL Translator or machine text composer like DeepL Write creating texts in the target language (formal emails, minutes or summaries) may take less time and give a more satisfactory effect both in terms of text quality and authors’ foreign language practice.
Keywords: NMT; DeepL Translator; DeepL Write; translation; postediting; plurilingual workplaces